2017
DOI: 10.1515/jpm-2015-0364
|View full text |Cite
|
Sign up to set email alerts
|

Delivery modes in case of fetal malformations

Abstract: An estimated 276,000 babies die within 4 weeks of birth every year, worldwide, from congenital anomalies. Better quality ultrasound screening can increase the detection of these fetal malformations in the prenatal period. Prenatal counseling for the pregnant woman and her family, regarding the nature of the disease and prognosis is necessary. Options for management in prenatal, perinatal, intrapartum, neonatal, and childhood periods need to be thoroughly discussed, so that the family can make an informed decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Also, we observed that delivery mode was not associated with adverse neonatal outcomes. Inconsistently, some observational studies suggesting that cesarean delivery may provide a better outcome for babies with meningomyelocele (MMC) existed [14]. These studies suggested that cesarean delivery would be beneficial by keeping MMC sac intact, reducing bacterial contamination of the exposed neural tissue and also allow for a better preparation of the team (i.e., neonatologist and pediatric neurosurgeons).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we observed that delivery mode was not associated with adverse neonatal outcomes. Inconsistently, some observational studies suggesting that cesarean delivery may provide a better outcome for babies with meningomyelocele (MMC) existed [14]. These studies suggested that cesarean delivery would be beneficial by keeping MMC sac intact, reducing bacterial contamination of the exposed neural tissue and also allow for a better preparation of the team (i.e., neonatologist and pediatric neurosurgeons).…”
Section: Discussionmentioning
confidence: 99%
“…In meetings, forums, and webinars, Secretariat representatives repeatedly reminded health care professionals and hospital administrators that unless some other complication arose that justified surgical delivery, women whose fetuses were diagnosed with microcephaly should give birth vaginally. Indeed, there is not enough evidence in the scientific literature to indicate that C-section improves neonatal outcomes for babies with microcephaly and other congenital malformations (Kuller et al 1996;Rio Grande do Sul 2016;Souza et al 2016;Wataganara et al 2017), 2 and there were no data about the relative risks and benefits of different modes of delivery in the specific case of CZS. Out of the 13 women in the cohort of mothers I interviewed who had given birth to children with CZS, however, all but three gave birth via cesarean.…”
Section: An Epidemic Within An Epidemic: Zikv and C-section In Brazilmentioning
confidence: 99%
“…2016; Wataganara et al. 2017), 2 and there were no data about the relative risks and benefits of different modes of delivery in the specific case of CZS. Out of the 13 women in the cohort of mothers I interviewed who had given birth to children with CZS, however, all but three gave birth via cesarean.…”
Section: An Epidemic Within An Epidemic: Zikv and C‐section In Brazilmentioning
confidence: 99%
“…This can reduce the risk of injury to the fetus from vaginal delivery. Although the risk of fetal loss is less relevant in this instance, the procedure may still cause women a range of significant health complications (Anteby and Yagel 2003; Hadar et al 2011; Häger et al 2004; Sutton 2008; Villar et al 2007; Wataganara et al 2017). In view of these issues, it remains unclear whether routinely offering women prenatal screening for fetal abnormalities would not in fact detract from the pursuit of Just health .…”
Section: Prenatal Screening and Just Healthmentioning
confidence: 99%